Environmental and Behavioral Factors Associated with the Presence of Aedes aegypti Larvae in the Sangurara Community Health Center Area, Palu City - Widiana Widiana; Kiki Sanjaya; Adhe Sofyan Anas; Nur Azizah Azzahra; Alchamdani Alchamdani; Riri Suwahyuni Wahid (Sean Institute, 2026)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus transmitted through the bite of the Aedes aegypti mosquito. The presence of mosquito larvae in the household environment is an important indicator in assessing the risk of transmission of this disease. According to the World Health Organization (WHO), there are approximately 390 million dengue virus infections worldwide each year, with approximately 96 million cases showing clinical manifestations. In Indonesia, DHF is a public health problem that continues to be monitored. In the working area of the Sangurara Community Health Center in Palu City, cases were recorded at 79 in 2022, increasing to 96 in 2023, and decreasing to 70 in 2024. This study aims to determine the relationship between temperature, humidity, and knowledge with the presence of Aedes aegypti mosquito larvae. This study employed a quantitative cross-sectional design using the Fisher's Exact Test and the Fisher Freeman Halton Exact Tes. The study population consisted of all household heads in the Sangurara Community Health Center working area totaling 13,591 families with a sample of 100 households. Data collection was carried out through examining larvae in all water containers in respondents’ homes and interviews using questionnaires. The results showed HI values of 20%, CI 23%, BI 40%, and ABJ 80% indicating a high larval density category. Bivariate analysis showed a significant relationship between temperature ( p = 0.016), humidity ( p = 0.039), and knowledge ( p = 0.012) with the presence of Aedes aegypti mosquito larvae. Knowledge was identified as the most influential factor associated with the presence of larvae. The conclusion shows that environmental factors (temperature and humidity) and knowledge are related to the presence of larvae so that it is necessary to strengthen larva surveillance and increase Mosquito Nest Eradication (PSN) practices by the community to reduce larva density and the risk of dengue transmission.